Legal Consequences Of Default In Land Sale And Purchase Agreements Under The Hand - Al Imron, Yunus (International Journal of Educational Research & Social Sciences, 2022)
The transfer of land rights can occur in accordance with the provisions of Article 20 paragraph (2) of the UUPA which contains provisions that property rights can be transferred and transferred, for example the death of the land owner. This legally makes the ownership rights to the land transfer to the heirs as long as they meet the requirements as the subject of property rights. The formulation of the problem: (1) Is buying and selling land under the law legal? (2) What are the factors that cause the sale and purchase of underhand land to still occur? (3) What are the legal consequences of both parties with the sale and purchase under the hand?. The research method used is normative juridical. The data source is primary data, secondary data. Data were collected by interview and literature study, data were analyzed using qualitative analysis. The results of this study (1) Although customary law confirms the legality of buying and selling land rights that are not carried out before the Land Deed Maker Official, in this case the buyer has difficulty proving his rights to the land he has purchased. (2) Factors that cause the sale buying land with ownership rights through private deeds for village communities: the community avoids quite expensive costs, second: community knowledge regarding the procedures for buying and selling land, third: community motivation related to the high level of mutual trust between each other in buying and selling land. (3) Village communities do a lot of buying and selling under their hands, namely buying and selling carried out in front of the village head, but if there are people who want to get a land certificate in his name, then resale is carried out in accordance with the applicable legal rules.